Expanding the Estimate of the Costs of Severe Maternal Morbidity to Include Readmissions, Physician Fees, and Infant Costs. (20th August 2020) - Phibbs, C.; Leonard, S.; Kozhimannil, K.; Main, E.; Phibbs, C.; Schmitt, S.; Lorch, S.
Abstract : Over the last 15 years, the United States has experienced major increases in the rates of severe maternal morbidity (SMM) or maternal "near misses." Initial estimates of the costs of SMM have used delivery hospitalization data, which exclude physician costs and hospital readmissions from the estimates. The objective of this study was to expand existing estimates of the costs of SMM to include readmissions and physician costs and to examine whether SMM had an effect on infant costs. Secondary data analysis. We used the CDC definition of SMM, including readmissions up to 42 days postpartum. GLM models with a gamma distribution and a log link were used to estimate the effect of SMM on costs, controlling for race/ethnicity, cesarean delivery, type of insurance, parity, maternal age and BMI, multiple births, and an obstetric severity index. The infant models also controlled for gestational age, infant gender, and serious congenital anomalies. Models were estimated with and without hospital fixed‐effects. California linked birth certificate‐patient discharge data for mothers and infants for 2009‐2011. About 200 000 were excluded for missing charge data (almost all insured by Kaiser Permanante). Cost‐to‐charge ratios were used to estimate costs from charges (including readmissions) and adjust for inflation to December 2017 dollars. Mean DRG‐specific reimbursement was used to estimate physician payments. The final sample was 1 262 862. A case of SMM increases delivery costs to a mean of about three times those of a normal, uncomplicated delivery, $7014 vs $20 756. The added costs were $10 396 for vaginal deliveries and $15 838 for c‐sections. Physician costs were over 20% of total SMM costs, $2290 (vaginal) and $3521 (cesarean), respectively. Including readmissions increased the SMM rate by 14.5%; these cases had a mean cost of $19 500, of which $4500 were MD costs. Mean infant costs were $23 318 with SMM and $6135 without, but this difference was much smaller for term deliveries ($5394 vs $2685). The risk‐adjusted estimate was that SMM increased maternal costs by 72% and 71% and infant costs by 27% and 32%, with and without hospital fixed‐effects, respectively. The per case maternal costs of SMM are triple those of a normal delivery. Further, readmissions and physician costs are important and previously unreported factors that add about $5000/case to the estimated maternal costs of SMM, increase the prevalence of SMM by 14.5%, and explain much of why our estimates are higher than previous reports ($6100‐8600). SMM is also associated with modest increases in infant costs. Projecting our costs to the entire United States results in $825 million in addition maternal costs; adjusting for California's higher costs still results in over $500 m in additional costs due to SMM. The costs of SMM extend well beyond those of the added costs of the delivery hospitalization. Failure to account for SMM‐associated readmissions or physician costs result in a meaningful under‐estimate of the costs of SMM. The additional infant costs associated with SMM need further investigation. National Institutes of Health.